THE BUCKWHEAT ROLE IN CROP ROTATION AND WEED CONTROL IN THIS SOWINGS IN LONG TERM TRIAL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Buckwheat research has been carried out within the long-term crop rotation stationary that was established in 1969 as a part of the Research institute of Agriculture. Buckwheat proportion within the partcular crop rotations went up to 22%. The highest buckwheat yields were obtained from the buckwheat variants that where cultivated after winter rye, and within the buckwheat monoculture experimental plots. A considerable yield decrease was observed when cultivating buckwheat after potatoes. Weeds in the buckwheat sowing were effectively brought under control by the herbicide Butisane 400 (1.5 l ha-1), applied immediately after sowing and Betanal AM 2.5 l ha-1 after seedling in 2-3 leaves stage.